Synthesis of Phospho‐Polypeptides via Phosphate‐Containing N‐Carboxyanhydride: Application in Enzyme‐Induced Self‐Assembly, and Calcium Carbonate Mineralization. Issue 5 (25th May 2020) - Mondal, Basudeb; Das, Soumen; Panda, Sidharth; Dutta, Tahiti; Gupta, Sayam Sen
Abstract: An easy synthetic strategy was developed to synthesize the phosphate‐functionalized amino acid N‐carboxyanhydride (NCA), using simple primary amine initiators to obtain homo and block phospho‐polypeptides with controlled molecular weight and molecular weight distribution. The methodology was extended to the synthesis of the end‐functionalized homo polypeptides (15 to 50 repeat unit) and block co‐polypeptides with PEG (0.7 K, 2 K, and 5 K) and glycopolypeptide (15‐unit mannose glycopolypeptide) as one of the blocks. The deprotected fully water‐soluble anionic phosphate‐based polypeptides showed pH‐dependent helical conformation with a helical content of 20 %, which further changed to β‐sheets upon addition of the enzyme alkaline phosphatase (ALP) due to dephosphorylation. The block co‐polypeptide containing PEG as one of the blocks led to its self‐assembly into colloidal structures, such as vesicles with a hydrodynamic diameter of ∼250 nm, due to the formation of amphiphilic block co‐polymer upon dephosphorylation. The nature of the colloidal structures formed can be temporally controlled by the extent of dephosphorylation. Finally, the phospho‐polypeptides serve as a template for the mineralization of calcium carbonate with varying polymorphs and morphologies. Abstract : On phospho‐polypeptides : An easy synthetic strategy was developed to synthesize phosphate‐functionalized polypeptides from an amino acid N‐carboxyanhydride (NCA). The deprotected phosphate‐based polypeptides displayed pH‐dependent helical conformation, which further changed to β‐sheet upon addition of the enzyme alkaline phosphatase (ALP). The block co‐polypeptide led to its self‐assembly into temporally controlled colloidal structures due to the formation of amphiphilic block co‐polymer upon dephosphorylation. Phospho‐polypeptides induce the mineralization of calcium carbonate with varying polymorphs and morphologies.